2009
DOI: 10.1080/17429140903243427
|View full text |Cite
|
Sign up to set email alerts
|

Phytoextraction of soil cadmium and zinc by microbes-inoculated Indian mustard (Brassica juncea)

Abstract: A pot experiment was carried out to evaluate the effect of Pseudomonas fluorescens and Trichoderma harzianum inoculation on the uptake of zinc (Zn) and cadmium (Cd) by Indian mustard (Brassica juncea) from the soil having three different concentrations of Zn (300, 600, 900 mg/kg) and Cd (5, 10, 15 mg/kg) separately. Microbial inoculation resulted in significantly better plant growth, available metal content and their uptake than control (without microbes). Available Zn was enhanced, ca.1.6-and 1.4-fold and Cd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The TI values on shoot length basis of inoculated plants were 81%, 69%, and 53% under 100 mg kg -1 , 200 mg kg -1 , and 300 mg kg -1 , respectively, whereas TI values on root length basis in the case of inoculated plants were 61%, 53%, and 49% under 100 mg kg -1 , 200 mg kg -1 , and 300 mg kg -1 , respectively. Some other studies also reveal the augmented TI in microbe-assisted mustard plants [34].…”
Section: Resultsmentioning
confidence: 99%
“…The TI values on shoot length basis of inoculated plants were 81%, 69%, and 53% under 100 mg kg -1 , 200 mg kg -1 , and 300 mg kg -1 , respectively, whereas TI values on root length basis in the case of inoculated plants were 61%, 53%, and 49% under 100 mg kg -1 , 200 mg kg -1 , and 300 mg kg -1 , respectively. Some other studies also reveal the augmented TI in microbe-assisted mustard plants [34].…”
Section: Resultsmentioning
confidence: 99%
“…A rising number of studies have demonstrated the application of Indian mustard and rapeseed in the phytoextraction of heavy metals, due to their capacity to accumulate high levels of Zn, Cu, Cd, and Se (Kuiper et al 2004; Ariyakanon and Winaipanich 2006; Grispen et al 2006; Chauhan and Rai 2009). Similarly, Chekol and Vough (2001), Kaimi et al (2007), Fan et al (2008), and Marti et al (2009) depicted alfalfa as a potential phytoremediator of organic contaminants, as well as its ability to germinate in petroleum-contaminated soil.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this fact, alternative biological clean-up methods, such as bioremediation and phytoremediation, have raised much interest in the last two decades. Moreover, a reasonable combination of both techniques is reflected by an emerging number of studies that utilize the natural degradation abilities of plants and plant-associated microorganisms to remove organic pollutants or heavy metals from the polluted environment (Liste and Felgentreu 2006; Gaskin et al 2008; Lin et al 2008; Chauhan and Rai 2009; Tang et al 2010). Rhizoremediation is a successful, cost-effective and environmentally friendly approach that is based on pollutant degradation to non- or less-toxic compounds by microorganisms in the rhizosphere.…”
Section: Introductionmentioning
confidence: 99%